A Proforma for Assessment of the Levels of Sanitation in Fish Processing Establishments - Iyer, T. S. Gopalakrishna; Kandoran, M. K. (Fishery Technology, 1972)
Over the past 15 years of its development, the fish processing industry in India has shown considerable improvement in maintenance of hygiene during handling of the raw material, processing and marketingof the finished product. This is best manifested in the lowering of upper limits of bacterial loads in factory environment and in processed products. Sanitation Score Forms form part of the day-to-day log sheets in fish processing establishments in Western countries.Based on the conditions available in India, a proforma for assessment of hygienic condition was prepared by this Institute recently. Trial tests were conducted which gave clear indication that a factory can easily score 65-70 marks when the minimum hygienic conditions aresatisfied. Keeping a daily record of the  hygienic conditions of the processing unit using such proforma will give the processor an idea about the hygienic conditions and can be helpful for further improvements.